Pengawetan Bambu dengan Metode Boucherie - Rumanintya Lisaria Putri; Lya Rochmawati; Dodi Nandika; I Wayan Darmawan (Jurnal Ilmu Pertanian Indonesia, 2020)
Bamboo is known as fast-growing species that could be derived into various products. However, bamboo is suspectible to the wood destroying organisms. Preservation is one way to improve the service life of bamboo. This study aimed to analyze the effect of differences in anatomical structures of betung bamboo (Dendrocalamus asper Backer) and andong bamboo (Gigantochloa pseudoarundinaceae (Steudel) Widjaja), and the effect of pressure on the flow time and retention of entiblu preservative in the Boucherie method. Bamboo stems with diameters of 10-14 cm were cut in 1; 1,5; 2; and 2,5 m lengths. The bamboo stems with moisture content of around 30% were preserved by 5% of entiblu preservative solution. The data observed were the flow time of the preservative entiblu solution from base of the stem until dripping on the top of the bamboo culm, and the retention of preservative. The anatomical structure of the bamboo trunk before preserving was also observed. The results showed that the average flow times in andong bamboo and betung bamboo were 37.75 minutes and 41.50 minutes, respectively. The average retention of entiblu solution on andong bamboo was 3.49 kg/m³ and on betung bamboo was 3.60 kg/m³. Keywords: andong bamboo, betung bamboo, anatomical structure, boucherie method, entiblu preservative